A quick method for evaluating the thresholds of workpiece surface damage in machining. Issue 1 (2019) - Xu, Dongdong; Liao, Zhirong; Axinte, Dragos; Hardy, Mark; M'Saoubi, Rachid
Abstract: This paper proposes a Pendulum-Based Cutting Test (PBCT) methodology which allows quick cutting tests for surface integrity evaluation along with providing cutting energies associated with particular level of workpiece surface damage, this is backed by an unified cutting energy model that links damage level of machined surface with energy partition in the cutting area. PBCT method could rapidly define the energy transferred to the workpiece that incurs particular magnitude of surface damage without using conventional machine tools and monitor the cutting process while only limited amount of materials is required. A demonstration of the proposed method is presented for Inconel718.